TSPAN7 Exerts Anti-Tumor Effects in Bladder Cancer Through the PTEN/PI3K/AKT Pathway - Yu, Xi; Li, Shenglan; Pang, Mingrui; Du, Yang; Xu, Tao; Bai, Tao; Yang, Kang; Hu, Juncheng; Zhu, Shaoming; Wang, Lei; Liu, Xiuheng (Frontiers in Oncology, 2021)
The tetraspanin protein superfamily participate in the dynamic regulation of cellular membrane compartments expressed in a variety of tumor types, which may alter the biological properties of cancer cells such as cell development, activation, growth and motility. The role of tetraspanin 7 (TSPAN7) has never been investigated in bladder cancer (BCa). In this study, we aimed to investigate the biological function of TSPAN7 and its therapeutic potential in human BCa. First, via reverse transcription and quantitative real-time PCR (qRT-PCR), we observed downregulation of TSPAN7 in BCa tissues samples and cell lines and found that this downregulation was associated with a relatively high tumor stage and tumor grade. Low expression of TSPAN7 was significantly correlated with a much poorer prognosis for BCa patients than was high expression. Immunohistochemistry (IHC) showed that low TSPAN7 expression was a high-risk predictor of BCa patient overall survival. Furthermore, the inhibitory effects of TSPAN7 on the proliferation and migration of BCa cell lines were detected by CCK-8, wound-healing, colony formation and transwell assays in vitro. Flow cytometry analysis revealed that TSPAN7 induced BCa cell lines apoptosis and cell cycle arrest. In vivo, tumor growth in nude mice bearing tumor xenografts could be obviously affected by overexpression of TSPAN7. Western blotting showed that overexpression of TSPAN7 activated Bax, cleaved caspase-3 and PTEN but inactivated Bcl-2, p-PI3K and p-AKT to inhibit BCa cell growth via the PTEN/PI3K/AKT pathway. Taken together, our study will help identify a potential marker for BCa diagnosis and supply a target molecule for BCa treatment.